The Measuring Ideal Accountability in Leaking Customer Personal Data as an Unlawful Act - Elmaila, Izzah; Kusumadara, Afifah; Djumikasih, Djumikasih (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
The aim of this research is first to identify cases of personal data leakage as unlawful acts that violate the law. Second, find an ideal concept for cases of leakage of bank customers' personal data based on the burden of proof. This article used a normative (doctrinal) method with statute and conceptual approach. The results of the research show that personal data leakage is a form of unlawful act that can be held accountable provided that the elements are met: the existence of the act, the act being against the law, the existence of an error or negligence (negiglence), the existence of a loss, and a causal relationship between the cause and the loss. Judging from the burden of proof and the applicable regulations, the concept of strict liability is an appropriate concept for cases of leakage of customer personal data because it is shifting the burden of proof so that business actors must prove that they are innocent.